Uporaba ultrazvoka z intravenskim vnosom ultrazvočnega kontrastnega sredstva pri otrocih - Kobal, Lucija (Medicinski razgledi, 2023)
The contrast-enhanced ultrasound is a newer diagnostic method with an increasing number of indications. The method is safe, accessible, fast, repeatable, does not involve ioni- zing radiation or the use of iodine contrast agent, and does not require special preparation of the patient, sedation, or anaesthesia. In the USA, the intravenous use of ultrasound contrast agents in children has been registered since 2016. In Europe, the use of ultrasound contrast agents in persons under 18 years of age is only registered for intracavitary administration during a voiding cystourethrography. Intravenous administration in children is thus used off-label with appropriate parental consent. According to many guidelines, contrast-enhanced ultrasound in children is recommended mainly for the assessment of focal changes in the liver and other parenchymal organs, such as the spleen and kidneys, in the blood supply assessment of various tissues, and for the examination of hemodynamically stable children after blunt abdominal trauma. According to current research, contrast-enhanced ultrasound is also useful in the diagnosis of certain lung diseases, evaluation of changes in the brain and many other conditions. In this article, we will present the basic characteristics of the contrast-enhanced ultrasound and its main indications in children.
Keywords: intravenous application; intravenski vnos; ultrasoun; ultrasound contrast agent; ultrazvočno kontrastno sredstvo; ultrazvok